2022
DOI: 10.1096/fj.202200169r
|View full text |Cite
|
Sign up to set email alerts
|

SIRT1 activity orchestrates ECM expression during hESC‐chondrogenic differentiation

Abstract: Epigenetic modification is a key driver of differentiation, and the deacetylase Sirtuin1 (SIRT1) is an established regulator of cell function, ageing, and articular cartilage homeostasis. Here we investigate the role of SIRT1 during development of chondrocytes by using human embryonic stem cells (hESCs). HESC‐chondroprogenitors were treated with SIRT1 activator; SRT1720, or inhibitor; EX527, during differentiation. Activation of SIRT1 early in 3D‐pellet culture led to significant increases in the expression of… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 8 publications
(13 citation statements)
references
References 71 publications
0
13
0
Order By: Relevance
“…This highlights the importance of specificity of selected activators to sirtuin family members. Smith et al (2022) recently used pellet culture to induce chondrogenic differentiation in human embryonic stem cells and found that activation of SIRT1 using 5 μM SRT1720 during pellet culture leads to increased collagen type II and aggrecan gene and protein expression, but reduced sGAG accumulation. This contrasts with our findings with mature freshly isolated bovine chondrocytes where we observed a decrease in total collagen with a 50 × lower dose of SIRT1720 ( Figure 7B ), indicating that the response to SIRT1 activation may depend on dose and the differentiation state of the chondroprogenitor cell or chondrocyte.…”
Section: Discussionmentioning
confidence: 99%
“…This highlights the importance of specificity of selected activators to sirtuin family members. Smith et al (2022) recently used pellet culture to induce chondrogenic differentiation in human embryonic stem cells and found that activation of SIRT1 using 5 μM SRT1720 during pellet culture leads to increased collagen type II and aggrecan gene and protein expression, but reduced sGAG accumulation. This contrasts with our findings with mature freshly isolated bovine chondrocytes where we observed a decrease in total collagen with a 50 × lower dose of SIRT1720 ( Figure 7B ), indicating that the response to SIRT1 activation may depend on dose and the differentiation state of the chondroprogenitor cell or chondrocyte.…”
Section: Discussionmentioning
confidence: 99%
“…Day 11 prechondrocytes were removed from tissue culture plastic and centrifuged in 14ml polypropylene tubes at 300 xRCF in day 11 medium for 5 minutes to sediment cells. Caps were left loose to enable gaseous transfer and tubes incubated for 3 days at 37˚C to facilitate the production of a spherical pellet, as detailed previously [12]. At day 11+3, medium was changed for chondrogenic-basal medium (CM) containing GDF5 (10 ng/mL), TGFβ3 (10 ng/mL) (Peprotech) and BMP2 (0.5x EC66).…”
Section: Chondrogenic Pellet Culturementioning
confidence: 99%
“…Samples were taken from both 2D and 3D culture as described previously [12]. Samples were transferred to RLT buffer directly and RNA extracted by use of a RNeasy QiAgen kit.…”
Section: Qrt-pcr Gene Transcriptional Analysismentioning
confidence: 99%
See 2 more Smart Citations